Psychodynamic university counseling: which factors predict psychological functioning after intervention? - Speranza, Anna Maria; Franchini, Costanza; Quintigliano, Maria; Andreassi, Silvia; Morelli, Mara; Cerolini, Silvia; Petrocchi, Chiara; Fortunato, Alexandro (Frontiers in Psychology, 2023)
University counseling centers represent important resources for personal development, and students are increasingly turning to them for help. The present study aimed at, first, evaluating changing in psychological functioning before and after a university counseling intervention and, second, exploring which psychological variables predicted the intervention outcome. For this purpose, 122 students who attended university counseling services were administered measures to assess personality traits, and measures to assess state variables - intended as contextual, rather than stable, alterations in functioning - such as anxiety, hopelessness and depression. Several Linear Mixed Models were performed to measure the differences between OQ-45 scores before and after the intervention (one for each OQ dimension and OQ total score); then, two steps of multiple regression analyses were performed. Significative reductions between pre-test and post-test OQ-45 scores were found, highlighting increased levels of well-being; personality traits seem not to be predictive of the intervention outcome, while state variables significantly contribute to the psychological wellbeing improvement after counseling intervention.